Analisis Kesulitan Dalam Membuat Karya Dua Dimensi Siswa Kelas 5 Sekolah Dasar - Mareta Wahyu Nur Hanifah; Della Ayu Puspita; Abdullah Fatkhi Fiddin; Cynthia Carla Ika Santoso (CV. ITTC INDONESIA, 2024)
Two-dimensional art is a work of art that only consists of length and width dimensions, without space dimensions. The main characteristic of two-dimensional works of art is that they can only be seen from one viewing direction. This research aims to identify and analyze the difficulties faced by grade 5 students at SD 3 Piji in two-dimensional fine arts activities, especially in drawing, coloring, forming, cutting and gluing. The research method used was qualitative with direct observation, documentation, and practice with 5th grade students at SD 3 Piji. The research results showed that most students had difficulty proportioning objects, lacked patience when coloring, had difficulty forming ships and leaves, had difficulty cutting, and had difficulty gluing. Factors such as a lack of understanding of art concepts, lack of fine motor skills training, and lack of support from teachers also contribute to these difficulties. This research provides recommendations for developing art learning methods that are more interactive and support the development of fine motor skills of grade 5 students at SD 3 Piji